2010
DOI: 10.1002/adfm.201000792
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Au‐Coated TiO2 Nanotube Arrays as Recyclable SERS Substrates for Multifold Organic Pollutants Detection

Abstract: A multifunctional Au‐coated TiO2 nanotube array is made via synthesis of a TiO2 nanotube array through a ZnO template, followed by deposition of Au particles onto the TiO2 surface using photocatalytic deposition and a hydrothermal method, respectively. Such arrays exhibit superior detection sensitivity with high reproducibility and stability. In addition, due to possessing stable catalytic properties, the arrays can clean themselves by photocatalytic degradation of target molecules adsorbed to the substrate un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
344
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(355 citation statements)
references
References 58 publications
10
344
0
1
Order By: Relevance
“…These studies demonstrated the key role of metal contact on top of the semiconductor fi lm for SERS-based quantitative measurements. [14][15][16] Despite recent advances with inorganic semiconductors, to the best of our knowledge, the employment of π-conjugated organic semiconductors for SERS applications has never been demonstrated in the literature. This is rather surprising since organic semiconductors exhibit exceptional charge transport/light manipulation properties and excellent contact formation with metals such as Au and Ag in various optoelectronic devices such as organic fi eld-effect transistors (OFETs), [17][18][19][20][21][22][23][24][25][26][27][28][29] organic light-emitting diodes (OLEDs), [ 30 ] and organic photovoltaics (OPVs).…”
Section: Introductionmentioning
confidence: 98%
“…These studies demonstrated the key role of metal contact on top of the semiconductor fi lm for SERS-based quantitative measurements. [14][15][16] Despite recent advances with inorganic semiconductors, to the best of our knowledge, the employment of π-conjugated organic semiconductors for SERS applications has never been demonstrated in the literature. This is rather surprising since organic semiconductors exhibit exceptional charge transport/light manipulation properties and excellent contact formation with metals such as Au and Ag in various optoelectronic devices such as organic fi eld-effect transistors (OFETs), [17][18][19][20][21][22][23][24][25][26][27][28][29] organic light-emitting diodes (OLEDs), [ 30 ] and organic photovoltaics (OPVs).…”
Section: Introductionmentioning
confidence: 98%
“…The photocatalyst can be a semiconductor, which can create electron-hole pairs under photo-illumination [7]. Additionally, in recent years, researchers have investigated the catalysts of oxides.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of the SWs or the LMR in modulating the total effective E field has been ignored or addressed inadequately. The fact that Ag-or AuNP-dispersed vertically aligned 1D NW/nanorods 10 supported on a 2D wafer, to be called 2.5D hereafter, are better SERS performers [11][12][13][14][15][16][17] indicates a role for both the LMR and the SWs; however, this role has not yet been reported. Such a study is difficult but immensely useful because the hybrid (metal-semiconductor) nanostructures can be used for a wide range of applications such as SERS, [16][17][18] photonics, 4,5 renewable energy 3 and biomedicine.…”
Section: Introductionmentioning
confidence: 93%